2020
DOI: 10.3390/rs12030395
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Light at Night is Related to Broad-Scale Stopover Distributions of Nocturnally Migrating Landbirds along the Yucatan Peninsula, Mexico

Abstract: The distributions of birds during migratory stopovers are influenced by a hierarchy of factors. For example, in temperate regions, migrants are concentrated near areas of bright artificial light at night (ALAN) and also the coastlines of large water bodies at broad spatial scales. However, less is known about what drives broad-scale stopover distributions in the tropics. We quantified seasonal densities of nocturnally migrating landbirds during spring and fall of 2011–2015, using two weather radars on the Yuca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 73 publications
2
19
0
Order By: Relevance
“…We counted fewer shearwaters in flight in the presence of an illuminated torch (flashlight), providing evidence for negative phototaxis. This is consistent with previous research, in which analysis of radar data revealed that some bird species avoid bright areas and aircraft lights while migrating 24 , 49 , 50 . Another study reported that adult Scopoli’s shearwaters might be perturbed from provisioning their chicks due to an outdoor disco event 46 , although the effects of disturbance from high-intensity light and sound were not experimentally separated.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We counted fewer shearwaters in flight in the presence of an illuminated torch (flashlight), providing evidence for negative phototaxis. This is consistent with previous research, in which analysis of radar data revealed that some bird species avoid bright areas and aircraft lights while migrating 24 , 49 , 50 . Another study reported that adult Scopoli’s shearwaters might be perturbed from provisioning their chicks due to an outdoor disco event 46 , although the effects of disturbance from high-intensity light and sound were not experimentally separated.…”
Section: Discussionsupporting
confidence: 93%
“…Finally, we compared our research to previous studies that investigated the effects of artificial light on the behaviour of birds with lights being constantly on 24 , 25 , 49 , 62 , 63 or turned off for a period of time (20 min in 64 or 135 s in 45 ). Even though the torch used in our experiment satisfied the definition of light pollution 1 , the light stimuli we produced differed from other light stimuli regularly encountered by Manx shearwaters (such as streetlights along the coast or illuminated vessels).…”
Section: Discussionmentioning
confidence: 99%
“…Our approach adopted a more straightforward process of elucidating the influence of en route synoptic weather, but future research could address that question by examining the relative influence of the different nights during which synoptic weather occurred on stopover densities. In addition, our results could be applied in the future to continental bird migration forecasting [24] and investigations into the effects of artificial light during migration [55,[89][90][91]. Ultimately, synoptic weather types are themselves models of more continuous components of the environment and due to the lack of fine-scale weather data presently available, we could not quantify the relative contributions of the components of the synoptic weather in our analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work by [174] expanded light exposure estimates for migrating birds in flight to continental spatial scales and with longitudinal baselines of ∼20 years. To date, analyses have focused on aggregated lighting from a given city as a whole (e.g., appropriate for birds flying at high altitudes [175]) or on very bright, point sources of light beamed towards the sky [171], that may trap birds during stopover events [176].…”
Section: Ecological Impacts Of Light Pollutionmentioning
confidence: 99%